Ecological impacts and potential hazards of nickel on soil microbes, plants, and human health - Muhammad, Rizwan (2024)
Nickel (Ni) contamination poses a serious environmental concern, particularly in developing countries: where, anthropogenic activities significantly contributes to Ni accumulations in soils and waters. The contamination of agricultural soils with Ni, increases risks of its entry to terrestrial ecosystems and food production systems posing a threat to both food security and safety. We examined the existing published articles regarding the origin, source, accumulation, and transport of Ni in soil environments. Particularly, we reviewed the bioavailability and toxic effects of Ni to soil invertebrates and microbes, as well as its impact on soil-plant interactions including seed germination, nutrient uptake, photosynthesis, oxidative stress, antioxidant enzyme activity, and biomass production. Moreover, it underscores the potential health hazards associated with consuming crops cultivated in Ni-contaminated soils and elucidates the pathways through which Ni enters the food chain. The published literature suggests that chronic Ni exposure may have long-term implications for the food supply chain and the health of the public. Therefore, an aggressive effort is required for interdisciplinary collaboration for assessing and mitigating the ecological and health risks associated with Ni contamination. It also argues that these measures are necessary in light of the increasing level of Ni pollution in soil ecosystems and the potential impacts on public health and the environment.